Teacher-Trainers’ Digital Competency in Using Microsoft Copilot and Grammarly for Campus Journalism Course - Charmaine Diane D. Magtangob (International Journal on Integrated Education, 2026)
This study examined teacher-trainers’ digital competency in using Microsoft Copilot and Grammarly for campus journalism courses and developed a DigCompEdu-aligned training framework that reframed routine drafting and editing into auditable, classroom-ready practices. Using a quantitative correlational-descriptive design, every instrument provided six and six domain scores respectively, group differences were compared using independent-samples t -tests and ANOVAs with Welch corrections in the case of significance, and interrelationship between Copilot/ Grammarly competencies were measured using a Pearson correlation. An expert content validation process and pilot reliability test were completed before the administration of a structured questionnaire to a purposely selected group of sixty campus journalism advisers, who clearly represented a larger population of one hundred at the Schools Division of Taguig City and the Pateros District II in compliance with occurrence of established ethical guidelines and informed consent. The results indicated a group which is predominantly at the early to mid-career stages, and with a high level of women-leaning respondents, mainly pursuing non-English specialization, and reported being well proficient on both tools. The strengths appeared regarding planning, writing, fast feedback, tone and clarity modulation, contrastive practices, and capture of evidence, but the competences in summarization, progress monitoring, facilitated reflection, lengthy diagnostics, and setting a goal were not supported. The differences between sexes, ages, educational levels, specialization, and experience in the selection of skills were not statistically significant. The observed positive correlation between Copilot and Grammarly skills highlighted the possibility of the existence of workflow habits that can be trained and shared. The findings informed the creation of the Magtangob Training Framework on Copilot–Grammarly Competency on the Campus Journalism, which is a quadrant-based model that combines Tandem Sprints (two-column traces), Assessment Trails (rubrics and ledgers), genre-specific resource packs with high-fidelity summaries, micro-conferences of five minutes, and peer-coaching clinics, which are aligned under the Sustainable Development Goal 4, 5, 9, and 16, ambisyon 204.